Inštitucionálne vymedzenie regionálneho rozvoja v procese reformy verejnej správy na Slovensku - Skyba, Radovan (Univerzita Pardubice, 2004)
The quality of the projects put forward into the European Union varies on a large scale depending on the country and experiences of the team. The success is result of the cooperation of citizens, specialists of the local authority, non-governmental sector and government administration. The contribution proposes to affect institutional conditions for high-quality handling of the regional development, which are assumption for such a wide synergy.
Keywords: Regionální politika; Regionální rozvoj; Slovensko; reforma veřejné správy